Peran Lembaga Internasional dalam Mewujudkan Perdamaian Global: Pelatihan Edukatif untuk Guru dan Siswa di Sekolah Indonesia Kuala Lumpur - Shiddiqy, Muhammad Arsy Ash; Novarizal, Riky; Daulay, Haniya Malafaiza; Rahmadani, Shalsa (Universitas Pahlawan Tuanku Tambusai, 2026)
Global peace is a shared aspiration that can only be achieved through cross-national collaboration and the role of international institutions. Education plays a strategic role in instilling peace values from an early age. This community service activity was conducted at the Indonesian School of Kuala Lumpur (SIKL) to enhance teachers and students understanding of the roles of international institutions such as the United Nations, UNESCO, UNICEF, and ASEAN in promoting global peace. The program included educational training, workshops, diplomacy simulations, and the preparation of peace-based learning plans. The results indicated a significant improvement in participants knowledge and skills in integrating global issues into learning. Furthermore, the program strengthened values of tolerance, cooperation, and social awareness within the school environment. This initiative serves as a model for implementing global education and character building in Indonesian schools abroad.